Substrate Utilization by Brown Adipose Tissue: What’s Hot and What’s Not? - McNeill, Ben T.; Morton, Nicholas M.; Stimson, Roland H. (Frontiers in Endocrinology, 2020)
Our understanding of brown adipose tissue (BAT) function in humans has increased rapidly over the past 10 years. This is predominantly due to the development of powerful non-invasive imaging techniques such as positron emission tomography that can quantify BAT mass and function using metabolic tracers. Activation of BAT during cold–induced thermogenesis is an effective way to dissipate energy to generate heat and requires utilisation of multiple energy substrates for optimal function. This has led to interest in the activation of BAT as a potential therapeutic target for type 2 diabetes, dyslipidaemia and obesity. Here we provide an overview of the current understanding of BAT substrate utilisation in humans and highlight additional mechanisms found in rodents, where BAT more prominently contributes to energy expenditure. During thermogenesis, BAT demonstrates substantially increased glucose uptake which appears to be critical for BAT function. However, glucose is not fully oxidised, with a large proportion converted to lactate. The primary energy substrate for thermogenesis is fatty acids, released from brown adipocyte triglyceride stores. Active BAT also sequesters circulating lipids to sustain optimal thermogenesis. Recent evidence reveals that metabolic intermediates from the tricarboxylic acid cycle and glycolytic pathways also play a critical role in BAT function. Understanding the role of these metabolites in regulating thermogenesis and whole body substrate utilisation may elucidate novel strategies for therapeutic BAT activation.